Effect of skimmed milk powder concentrations on the biological characteristics of microencapsulated Saccharomyces cerevisiae by vacuum-spray-freeze-drying. Issue 4 (11th March 2020) - Cao, Lin; Xu, Qinglian; Xing, Yage; Guo, Xunlian; Li, Wenxiu; Cai, Yimin
Abstract: The effects of skimmed milk powder (SMP) concentrations on the biological characteristics of microencapsulated Saccharomyces cerevisiae prepared by employing vacuum-spray-freeze-drying (VSFD) technology are evaluated. Results show that the live bacteria rate of S. cerevisiae embedded with 11% SMP is 76.36%, which is higher than that in other concentrations. Scanning electron microscope (SEM) photographs indicate that the SMP concentration exhibits a significant impact on the surface morphology of microencapsulation. Moreover, microparticles with SMP at the concentration of 11% provide the highest stability levels in both high and low temperature conditions. Cell counts in the microparticles with 11% SMP show a reduction of 3.9 (60 °C, 20 min) log CFU mL −1, 3.13 (50 °C, 20 min) log CFU mL −1, 0.23 (40 °C, 20 min) log CFU mL −1, 2.74 (4 °C, week) and 0.72 (10 °C, week) log CFU mL −1, respectively, which are all lower than that of powders with 3% SMP. Furthermore, the best-quality icewine exhibiting the typical features of a fresh fragrance and a delicate taste is used for the in vivo fermentation process. Fermentation is initialized by the microencapsulated cells with 11% SMP. These results indicate that the complex materials containing an SMP concentration of 11% as a carrier can be considered as a better choice for improving the stability and survival rate of S. cerevisiae .